DDIT4 S‐Nitrosylation Aids p38‐MAPK Signaling Complex Assembly to Promote Hepatic Reactive Oxygen Species Production. Issue 18 (26th July 2021) - Li, Zilong; Zhao, Qianwen; Lu, Yunjie; Zhang, Yangxi; Li, Luyang; Li, Min; Chen, Xuemin; Sun, Donglin; Duan, Yunfei; Xu, Yong
Abstract: Mitogen‐activated protein kinase (MAPK) signaling plays a significant role in reactive oxygen species (ROS) production. The authors have previously shown that Brahma‐related gene 1 (BRG1), a chromatin remodeling protein, contributes to hepatic ROS accumulation in multiple animal and cellular models of liver injury. Here it is reported that DNA damage‐induced transcript 4 (DDIT4) is identified as a direct transcriptional target for BRG1. DDIT4 overexpression overcomes BRG1 deficiency to restore ROS production whereas DDIT4 knockdown phenocopies BRG1 deficiency in suppressing ROS production in vitro and in vivo. Mechanistically, DDIT4 coordinates the assembly of the p38‐MAPK signaling complex to drive ROS production in an S‐nitrosylation dependent manner. Molecular docking identifies several bioactive DDIT4‐inteacting compounds including imatinib, nilotinib, and nateglinide, all of which are confirmed to attenuate hepatic ROS production, dampen p38‐MAPK signaling, and ameliorate liver injury by influencing DDIT4 S‐nitrosylation. Importantly, positive correlation between ROS levels and BRG1/DDIT4/S‐nitrosylated DDIT4 levels is detected in human liver biopsy specimens. In conclusion, the data reveal a transcription‐based signaling cascade that contributes to ROS production in liver injury. Abstract : Brahma‐related gene 1 interacts with hypoxia inducible factor‐1 α to activate the transcription of DNA damage‐induced transcript 4 (DDIT4) in hepatocytes in response to injurious stimuli. DDIT4 undergoes S‐nitrosylation at a conserved cysteine residue, which licenses DDIT4 to be incorporated into the p38‐MAPK signaling complex. The ensuring p38 activation leads to accelerated reactive oxygen species production and liver injury.